Sperm DNA Methylation at Metabolism-Related Genes in Vegan Subjects - Franzago, Marica; Sabovic, Iva; Franchi, Sara; De Santo, Maria; Di Nisio, Andrea; Luddi, Alice; Piomboni, Paola; Vitacolonna, Ester; Stuppia, Liborio; Foresta, Carlo (Frontiers in Endocrinology, 2021)
Objective: To investigate if epigenome of sperm cells could be dynamically affected by nutrition. Design and methods: We assessed 40 healthy volunteers with different dietary habits and collected their demographic characteristics, as well as clinical and anthropometric parameters. We compared methylation profiles in sperm quantified by bisulfite pyrosequencing, at promoter-associated CpG sites of genes involved in metabolism including FTO and MC4R from 6 vegans and 34 omnivores. In addition, the FTO rs9939609 (T>A) was genotyped. Results: Higher DNA methylation levels were detected in the sperm of vegan at FTO gene CpG1 [p=0.02], CpG2 [p=0.001], CpG3 [p=0.004] and CpG4 [p=0.003] sites and at MC4R-CpG2 site [p=0.016] as compared to sperm of omnivores. This association was not related to FTO genotype. Conclusions: Although limited by the small number of investigated cases, our data provide insight into the role of diet on sperm DNA methylation in genes involved in metabolism.